A preponderance of gastrointestinal cancer patients transition into cachexia syndrome. Issue 6 (27th September 2022) - Gilmore, Linda Anne; Olaechea, Santiago; Gilmore, Brian W.; Gannavarapu, Bhavani S.; Alvarez, Christian M.; Ahn, Chul; Iyengar, Puneeth; Infante, Rodney E.
Abstract: Background: Cancer cachexia is frequently documented by self‐reported, single time‐point weight histories. This approach lacks the granularity needed to fully elucidate the progression of cachexia syndrome. This study aimed to longitudinally assess body weight changes pre‐ and post‐cancer diagnosis in gastrointestinal (GI) cancer patients. Methods: Body weights and relevant clinical data recorded in the electronic health record 12 months pre‐ and post‐GI cancer (colorectal, gastroesophageal, hepatobiliary and pancreatic) diagnosis were extracted. Weight loss was categorized by the International Consensus Definition for cachexia. Results: A total of 879 patients were included in the final cohort including patients diagnosed with colorectal ( n  = 317), hepatocellular ( n  = 185), biliary ( n  = 72), pancreatic ( n  = 186) or gastroesophageal ( n  = 119) cancer. Stage of disease was equally distributed. Patients without cachexia at diagnosis ( n  = 608) remained weight stable during the 12 months pre‐diagnosis (+0.5 ± 0.5% body weight; P  = 0.99). Patients with cachexia at diagnosis ( n  = 271) remained weight stable 6 to 12 months prior to diagnosis (+0.4 ± 0.8%; P  > 0.9999) and lost 8.7 ± 0.6% ( P  < 0.0001) within the 6 months pre‐diagnosis. Patients without cachexia at diagnosis lost more weight post‐diagnosis (6.3 ± 0.6%) than patients with cachexia at diagnosis (4.7 ± 1.0%; P  = 0.01). Pre‐diagnosis weight trajectories did not differ between primary malignancies or stage of disease in patients without or with cachexia at diagnosis (all P  ≥ 0.05). Post‐diagnosis weight trajectories did differ by primary malignancy ( P  ≤ 0.0002) and stage ( P  < 0.0001). In both patients without and with cachexia at diagnosis, colorectal patients lost the least amount of weight post‐diagnosis and gastroesophageal patients lost the most amount of weight post‐diagnosis. Stage 4 patients without or with cachexia at diagnosis lost the most weight post‐diagnosis ( P  ≤ 0.0003). Regardless of cachexia status at diagnosis, patients lost more weight when treated with systemic therapy (7.1 ± 0.7%; P  < 0.0001; n  = 419) or radiation therapy (8.4 ± 1.4%; P  = 0.02; n  = 116) compared to those who did not. Patients who did not have surgery lost more weight post‐diagnosis (7.6 ± 1.1%; P  < 0.0001; n  = 355) compared to those who did have surgery. By 12 months post‐diagnosis, 83% of the surviving GI cancer patients in this cohort had transitioned into cachexia syndrome. Conclusions: Significant weight loss in patients with GI cancer cachexia at diagnosis initiates at least 6 months prior to diagnosis, and most patients will transition into cachexia syndrome post‐diagnosis, regardless of pre‐diagnosis weight change and stage of disease. These findings punctuate the importance of weight surveillance in cancer detection and earlier palliative interventions post‐diagnosis in the GI cancer patient population.